2021
DOI: 10.3389/fevo.2021.679673
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pathways of Climate Change Effects in SpaDES: An Application to Boreal Landbirds of Northwest Territories Canada

Abstract: Distributions of landbirds in Canadian northern forests are expected to be affected by climate change, but it remains unclear which pathways are responsible for projected climate effects. Determining whether climate change acts indirectly through changing fire regimes and/or vegetation dynamics, or directly through changes in climatic suitability may allow land managers to address negative trajectories via forest management. We used SpaDES, a novel toolkit built in R that facilitates the implementation of simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 76 publications
0
53
0
Order By: Relevance
“…Immediate effects that were expressed through the change in climate conditions apparently strongly modified the assemblage composition more than did the lagged effects. In fact, the difference in magnitude between the two effects was due to the mismatch that was generated by rapid climate variation compared to slower vegetation change (Wu et al, 2015; Stralberg et al, 2015; Micheletti et al, 2021). Regionally, both climate effects acted on the decrease in number of winner species and on the increase in assemblage dissimilarity by ordered comparison of RCP 4.5 through RCP 8.5 to the baseline scenario.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Immediate effects that were expressed through the change in climate conditions apparently strongly modified the assemblage composition more than did the lagged effects. In fact, the difference in magnitude between the two effects was due to the mismatch that was generated by rapid climate variation compared to slower vegetation change (Wu et al, 2015; Stralberg et al, 2015; Micheletti et al, 2021). Regionally, both climate effects acted on the decrease in number of winner species and on the increase in assemblage dissimilarity by ordered comparison of RCP 4.5 through RCP 8.5 to the baseline scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that indirect effects, through climate-induced changes in habitat only, were smaller in magnitude compared to the combined indirect and direct effects for both taxa. This conclusion can be explained by the mismatch between the climate and the biota (Stralberg et al, 2015; Wu et al, 2015; Micheletti et al, 2021). For example, Brice et al (2020) noted that under climate change the variation in climate conditions would be faster than the capacity of tree species to migrate, which creates a gap between the climatic niche and the observed distribution of species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations